Consanguinity and childhood acute lymphoblastic leukaemia: a case-control study - Ameer Kakaje; Mohammad Marwan Alhalabi; Ayham Ghareeb; Bahjat Karam; Bassam Mansour; Bayan Zahra; Othman Hamdan (SpringerOpen, 2022)
Abstract Background Consanguineous marriage is widely practised across the world. Its effect on acute lymphoblastic leukaemia (ALL) is controversial as both parents share some of the genes which might increase the incidence of sharing recessive genes. However, other theories suggest that consanguinity might have a protective factor as it does for other types of cancers. This study aims to study childhood ALL and consanguinity. Methods This is a case-control study, conducted in the major paediatric hospital in Damascus, Syria, using medical records. Case group included children with ALL, while control group included other patients and were matched by gender and age. Results This study comprised 386 patients, 193 of which were cases. Overall, 136 were of consanguineous marriages (36.8%), and there was no difference in consanguinity overall between cases and controls. However, when only comparing non-consanguineous parents and fourth-degree consanguinity, fourth degree was significantly higher among case group, suggesting a negative correlation OR = 0.387 (0.187-0.801) in contrast to third-degree consanguinity which was no significantly different when comparing the two groups (p > 0.05). We found no significant association between ALL and having a family history of cancer (p > 0.05) or between parents' educational level and case-control groups (p > 0.05). Conclusion Our research suggests a negative association between fourth-degree consanguinity and childhood leukaemia. This was not observed with a third-degree consanguinity. Previous studies had contradicting data on consanguinity and ALL which demonstrates the need for further research.